Biocompatibility evaluation of the PCL polymer covering the Ti-30Ta alloy (Research, Society and Development, 2020)
Nowadays, researches have been investigated new materials for biomedical applications. The aim of this study iso optimize the behavior of the material / biological environment interface. Among the most used materials are titanium and its alloys due to properties such as resistance to corrosion and biocompatibility. Studies have shown cellular behavior can be influenced by surface morphology. Therefore, the objective of this study was to associate the deposition of PCL polymer fibers with the growth of TiO2 nanotubes on the surface of the Ti-30Ta alloy for biomedical applications. The electrospinning process was used for the production of 200nm polymer nanofibers. The use of biocompatible polymers for the viability of cell growth is a promising alternative to improve osseointegration. Characterization techniques such as scanning electron microscopy (SEM-FEG) were used to investigate the surface of the samples. Adult stem cells derived from human adipose tissue (ADSC) were also used to study the cellular response of these biomaterials. Cell viability was determined by the Cell Titer-Blue assay after 1 and 7 days. The results indicated the nanoarchitecture of the nanostructures in the micro-topography has a is a promising in the biomedical field.